ANALYSIS OF CODE SWITCHING USED BY DEDDY CORBUZIER ON HITAM PUTIH PROGRAM IN TRANS7 - Ari Nuryandi; Rizki Ridho Rahardja (PROJECT (Professional Journal of English Education), 2018)
Abstract Used two or more languages within an utterance or what linguists call code switching, fairly common especially between two of the most languages when speaking in public. The code switching often done by someone when he was talking to someone else or talking in front of the public in particular person who mastery more than one language. Deddy Corbuzier always do code switching when speaking or explain topic particular, so topic submitted more interesting.This study aims to analyze the type of code switching used by Deddy Corbuzier on Hitam Putih program in Trans7 and also describe Deddy Corbuzier do code switching based on the theory of Romaine and Hoffman. The writer also analyze the type and the reason  code switching of the most dominant frequently by Deddy Corbuzier.The method in this study the writer uses qualitative descriptive and also use the case study to analyze and describe the type and the reason Deddy Corbuzier do code switching on Hitam Putih program in Trans7.A result of the research was conducted by the author shows Deddy Corbuzier more dominant code switch type of  Inter-sentential switching compared other type code switching and the reason for the most dominant Deddy do code switching is quoting somebody else. Keywords: Analysis, Code Switching, Deddy Corbuzier